Antioxidant properties of topical Caulerpa sp. extract on UVB-induced photoaging in mice - Anak Agung Gde Putra Wiraguna; Wimpie Pangkahila; I. Nyoman Mantik Astawa (PAGEPress Publications, 2018)
Caulerpa sp., a genus of seaweed native to the Indo-Pacific region, has been known for its antioxidant properties and health benefits when consumed as food. Previous studies have reported Caulerpa sp.'s potential as a strong antioxidant, but its effects on the skin in a topical preparation, especially its role in UV protection, have not been studied extensively. Our study investigated the protective effects of 0.2% and 0.4% Caulerpa sp. extract gels on photoaging in the UVB-irradiated skin of Wistar mice. The subjects were divided into naive control, vehicle control, and 3 treatment groups (0.2% Caulerpa sp. extract gel, 0.4% Caulerpa sp. extract gel, and 0.02% astaxanthin gel as a standard antioxidant). The groups, except the naive control group, received a total of 840 mJ/cm2 of UVB irradiation in four weeks. Protective effects of the extract were measured through the evaluation of collagen expression, MMP-1 expression and levels, and 8-OhDG expression. Mice who received topical application of Caulerpa sp. extract gel had higher collagen expression, betterpreserved collagen structure, lower levels of MMP-1, and less MMP-1 and 8-OHdG expressions compared to the vehicle control group. There was no difference between different concentrations of the extract. Our findings demonstrated that topical application of Caulerpa sp. extract gel significantly protected UVB-irradiated mice skin from photoaging.